Investigation of the Amyloid β (12-28) Peptide Self-Recognition by Saturation Transfer Difference and Off-Resonance Relaxation NMR - Huang, Hao (My University, 2005)
The formation of soluble amyloid oligomers by polypeptide chains is the main pathogenic mechanism underlying several neurodegenerative disorders including some of the most common debilitating and aging-related illnesses such as Alzheimer's and Parkinson's diseases. However, the molecular basis of polypeptide oligomerization and amyloid formation is currently not fully understood. In this thesis the focus will be on the early steps of oligomer formation that precede the nucleation of amyloid fibrils, that are still reversible. The reversibility of these initial self-association equilibria makes them an attractive target for therapeutic intervention in the treatment of amyloid diseases. Specifically three general questions will be addressed: (a) What are the residues within a given polypeptide chain that mediate self-recognition? (b) What are the driving forces for self-association? (c) Is self-recognition coupled with conformation changes?
The objective of this thesis is to provide initial responses to these key questions using as prototypical system the Ap (12-28) peptide, which has been previously proposed as a model for the initial self-association events that are linked to Alzheimer's disease. Given the flexibility of this peptide the main tool for its investigation will be Nuclear Magnetic Resonance (NMR) spectroscopy. Specifically, both classical (i.e., TOCSY and NOESY) and more novel (i.e. saturation transfer difference and off-resonance relaxation) NMR experiments were used to probe the soluble oligomers through the comparative analysis of samples with different monomer/oligomer distributions. The combined analysis of this integrated set of experiments reveals that while the residues in the central hydrophobic core (CHC) drive self-recognition, stable oligomers require a conformational change towards more folded structures that affects residues well outside the CHC. The conformational change occurring upon self-association thus effectively couples CHC and non-CHC residues. This model may also explain why mutations outside the CHC (i.e. E22, D23) can affect significantly the kinetics of self-association.
Keywords: Amyloid; Peptide; Saturation Transfer; Relaxation NMR